Shrines of Holy women in the land of Khorezm and their educational importance today (Journal of Pedagogical Inventions and Practices, 2023)
The role and significance of sacred places and shrines, which are one of the main pillars of the national spiritual heritage of the Uzbek people, in the upbringing of the younger generation are incomparable. This article reveals the shrines in the Khorezm region, which for several centuries have been passed down from ancestors to generations as a spiritual treasure, and their importance in the education of young people